AKTIVITAS ANTIDIABETES EKSTRAK AIR Coriandrum Sativum PADA MENCIT JANTAN - S. D.S Banjarnahor; I.D Dewijanti; M Angelina; Salahudin Salahudin (Jurnal Kimia Terapan Indonesia, 2009)
Antidiabetic activity of aqueous extract from coriandrum sativum had been evaluated by using glucose tolerance test in mice. Mice were divided into five groups randomly and each group consists of six animals. In the glucose tolerance test on mice, 30, 60, 120 and 180 minutes after the administration of the extract at a dose of 8 mg/kgbb, serum glucose concentration decreased by 17.07%, 26.31%, 31.3% and 32.55% respectively. Antidiabetic activity of theextract showed no significant changes to that of control group (p<0.05).Keywords : Coriandrum sativum, water extract, glucose tolerance test, blood glucose level.